Patients with affective disorders profit most from telemedical treatment: evidence from a naturalistic patient cohort during the COVID-19 pandemic - Rohrmann, Tobias; Praus, Peter; Proctor, Tanja; Benedyk, Anastasia; Tost, Heike; Hennig, Oliver; Meyer-Lindenberg, Andreas; Wahl, Anna-Sophia (Frontiers in psychiatry, 2022)
Background: During the COVID-19 pandemic telemedicine became essential in maintaining diagnostic procedures and treatment in psychiatry. However, it is still an open question if telemedicine is a feasible treatment option for all groups of psychiatric patients alike. This prospective monocentric observational trial was conducted to assess the general applicability of telemedical treatment in a naturalistic psychiatric outpatient cohort and to identify groups of disorders and clusters of psychopathology that respond particularly well to telemedical treatment considering sociodemographic characteristics and patients' perspectives. Methods: Patients were recruited April 2020-April 2021 and asked to fill out the WHO-5 and the SCL-90R at baseline, after 4-6 and 8-12 weeks and a feedback-survey. Additionally, medical records, psychopathology, psychosocial functioning, and socio-demographic data were analyzed. Primary outcomes were well-being, psychopathology and functioning during treatment. Secondly, diagnostic groups and psychopathology linked to a superior treatment-response were determined with respect to patients' subjective experiences. Results: Out of 1.385 patients, 254—mostly with hyperkinetic (35.3%) and depressive disorders (24.6%)—took part. Well-being and SCL-90R total scores improved substantially (both p < 0.001). CGI and GAF scores were worse in depressed subjects (both p < 0.05). Improvement was mainly seen in depressed patients; chronic disorders experienced a decline in well-being. Sociodemographic characteristics could not explain this difference. Particularly female (r = 0.413) patients found telepsychiatry equivalent to conventional treatment. The more virtual sessions participants attended the more likely they were to find telepsychiatry equal to conventional treatment (r = 0.231).Conclusion: Telemedicine is an effective treatment for patients with depression under naturalistic conditions. Telemedical consultations are a simple and reliable way of monitoring symptom severity and directing treatment choices during the treatment of depressive disorders. Patients with depression benefited more from telemedical treatment compared to participants with chronic non-episodic psychiatric disorders. Future research needs to concentrate on improving telemedical treatment options suited for the latter conditions. Psychiatric telemedicine yielded overall high degrees of satisfaction among users.
Gesehen am 20.01.2023